2021
DOI: 10.3390/antibiotics10070839
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanoparticles Enhance Antimicrobial Efficacy of Antibiotics and Restore That Efficacy against the Melioidosis Pathogen

Abstract: Melioidosis is an infectious disease caused by Gram-negative bacillus bacteria Burkholderia pseudomallei. Due to the emerging resistance of B. pseudomallei to antibiotics including ceftazidime (CAZ), the development of novel antibiotics and alternative modes of treatment has become an urgent issue. Here, we demonstrated an ability to synergistically increase the efficiency of antibiotics through their combination with silver nanoparticles (AgNPs). Combinations of four conventional antibiotics including CAZ, im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 70 publications
1
14
0
Order By: Relevance
“…The maximum wavelength obtained (410.33 nm) when ultraviolet-visible spectroscopy of conjugated silver nanoparticles was determined in line with the studies carried out by Kasthuri et al (2009); Malawong et al (2021), which obtained similar results (Table 2). The size distribution of CAgNPs revealed an average size of 237.8 d.nm and was confirmed by the TEM image shown in Figure 3.…”
Section: Discussionsupporting
confidence: 85%
“…The maximum wavelength obtained (410.33 nm) when ultraviolet-visible spectroscopy of conjugated silver nanoparticles was determined in line with the studies carried out by Kasthuri et al (2009); Malawong et al (2021), which obtained similar results (Table 2). The size distribution of CAgNPs revealed an average size of 237.8 d.nm and was confirmed by the TEM image shown in Figure 3.…”
Section: Discussionsupporting
confidence: 85%
“…This may subsequently alter cell surface permeability, leading to the death of bacteria and fungi [ 399 ]. In addition, aminoglycoside antibiotics (e.g., gentamicin, neomycin, paromomycin) that are positively charged at physiological pH can synergize with all kinds of MNPs [ 400 , 401 ]. On the other hand, depending on their zeta potential, phytocomponents that act as stabilizing and capping agents can reduce the propensity of biosynthesized nanoparticles to aggregate, which influences their size, shape, stability and biological activity [ 392 , 402 ].…”
Section: Methods For Testing Antibacterial and Antifungal Activities ...mentioning
confidence: 99%
“…The combined use of AgNPs and classic antibiotics may help to decrease the concentrations needed and perhaps the cytotoxic effects, as shown in [ 78 ]. This can also be useful for the recovering of antibiotics not used because of high levels of pathogen resistance, toxic effects on bacterial hosts, and perhaps the impossibility of reaching sufficient concentrations in the host’s fluids or tissues for effective activity [ 39 , 41 , 42 , 79 ]. Mechanisms involved in AgNPs–antibiotic synergy have not been extensively studied, but some authors have correlated this phenomenon with the existence of an interaction between both components, which generates complexes that interact better with the bacterial envelopes and produce a higher release of Ag + from the AgNPs [ 80 ], but the possibility of other mechanisms involving the proprietary mechanisms of each of the agents should not be ignored.…”
Section: Resultsmentioning
confidence: 99%
“…This would allow us, if synergy occurs, to use lower concentrations of antibiotics and AgNPs than when they are used alone [ 39 , 40 ]. Moreover, recent studies have shown that AgNPs can be used to recover the use of certain classical antibiotics not regularly used because of their toxic effects or resistance [ 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%